Pesticide Mixtures in Surface Waters of Two Protected Areas in Southwestern Germany - Anna Schemmer; Jakob Wolfram; Alexis. P. Roodt; Sascha Bub; Lara L. Petschick; Larissa Z. Herrmann; Sebastian Stehle; Ralf Schulz (Bulletin of Environmental Contamination and Toxicology, 2024)
Pesticides enter non-target surface waters as a result of agricultural activities and may reach water bodies in protected areas. We measured in southwestern Germany pesticide concentrations after heavy rainfalls in streams of a drinking water protection area near Hausen (Freiburg) and in the catchment of the Queich (Landau), which originates from the biosphere reserve Palatinate Forest. On average, 32 (n = 21) and 21 (n = 10) pesticides were detected per sample and event in the area of Hausen (n = 56) and in the Queich catchment (n = 17), respectively. The majority of pesticides detected in > 50% of all samples were fungicides, with fluopyram being detected throughout all samples. Aquatic invertebrates exhibited highest risks with 16.1% of samples exceeding mixture toxicity thresholds, whereas risks were lower for aquatic plants (12.9%) and fish (6.5%). Mixture toxicity threshold exceedances indicate adverse ecological effects to occur at half of sites (50%). This study illustrates the presence of pesticide mixtures and highlights ecological risks for aquatic organisms in surface waters of protected areas in Germany.

Diversified innovations in the health sciences: Proposal for a Diversity Minimal Item Set (DiMIS) - Gertraud Stadler; Marie Chesaniuk; Stephanie Haering; Julia Roseman; Vera Maren Straßburger; Schraudner Martina; Ahmad Aisha-Nusrat; Auma Maisha; Banas Kasia; Borde Theda; Buspavanich Pichit; Dewey Marc; et al. (Sustainable Chemistry and Pharmacy, 2023)

Neonicotinoid insecticides in global agricultural surface waters – Exposure, risks and regulatory challenges - Sebastian Stehle; Viktoriia Ovcharova; Jakob Wolfram; Sascha Bub; Larissa Zoë Herrmann; Lara Luisa Petschick; Ralf Schulz (Science of The Total Environment, 2023)

Methyleugenol DNA adducts in human liver are associated with SULT1A1 copy number variations and expression levels - Roman Tremmel; Kristin Herrmann; Wolfram Engst; Walter Meinl; Kathrin Klein; Hansruedi Glatt; Ulrich M. Zanger (Archives of Toxicology, 2017)

An experimental approach to Neolithic shifting cultivation - Manfred Rösch; Otto Ehrmann; Ludger Herrmann; Erhard Schulz; Arno Bogenrieder; Johann Peter Goldammer; Matthias Hall; Hans Page; Wolfram Schier (Vegetation History and Archaeobotany, 2002)